2019
DOI: 10.1016/j.flatc.2019.100112
|View full text |Cite
|
Sign up to set email alerts
|

Interlayer decoupling in twisted bilayers of β-phosphorus and arsenic: A computational study

Abstract: We investigate magnetism and band structure engineering in Moiré superlattice of blue phosphorus (β-P) and grey arsenene (β-As) bilayers, using ab initio calculations. The electronic states near the valence and conduction band edges have significant pz character in both the bilayers. Thus, twisting the layers significantly reduce the interlayer orbital overlap, leading to a decrease in the binding energy (up to ∼ 33%) and an increase in interlayer distance (up to ∼ 10%), compared to the most stable AA-stacking… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…In this respect, the results are similar to those reported for the other pnictogens, phosphorous and arsenic, both beta-phase bilayers. 22,23 This is interesting since unconventional superconductivity 1 and insulating strongly correlated states 2 are ascribed to the existence of at bands below the Fermi level in twisted structures, but only for very small magic angles. The emergence of at bands in the relatively greater twist angles shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, the results are similar to those reported for the other pnictogens, phosphorous and arsenic, both beta-phase bilayers. 22,23 This is interesting since unconventional superconductivity 1 and insulating strongly correlated states 2 are ascribed to the existence of at bands below the Fermi level in twisted structures, but only for very small magic angles. The emergence of at bands in the relatively greater twist angles shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[28][29][30] To date, the band structures of the β-P, β-As, and β-Sb twisted systems have also been explored by density functional theory (DFT) methods. [31][32][33][34] An et al found that the flat bandwidth of 10 meV in β-Sb appeared at 6.01 ○ . 34 Agnihotri et al studied the evolution of interlayer coupling in twisted bilayers of β-P and β-As, resulting in significant changes in the bandgap.…”
mentioning
confidence: 99%
“…34 Agnihotri et al studied the evolution of interlayer coupling in twisted bilayers of β-P and β-As, resulting in significant changes in the bandgap. 31 However, due to limited computational resources, investigations have been limited to the small system with an angle of 3.89 ○ and 868 atoms. Larger systems with thousands of atoms remain largely unexplored.…”
mentioning
confidence: 99%
See 1 more Smart Citation